Impact of distal or pylorus preserving gastrectomy on postoperative quality of life in T1 stage middle third gastric cancer patients - Hao Chen; Siqing Jing; Zhaoping Li; Lianlian Cao; Wenxian Guan; Xin Chen; Meng Wang (Scientific Reports)
Abstract Pylorus-preserving gastrectomy (PPG) and distal gastrectomy (DG) are widely utilized surgical approaches for the treatment of gastric cancer. In this study, we employed questionnaire surveys and follow-up assessments to examine the effects of these surgical procedures on postoperative quality of life and pancreatic exocrine function in patients with stage T1 middle-third gastric cancer. A retrospective cohort study was conducted to analyze clinical and follow-up data from 63 gastric cancer patients who underwent distal gastrectomy and 21 who underwent pylorus-preserving gastrectomy at Nanjing University Drum Tower Hospital between January 2019 and January 2023. Patients were categorized into two groups: distal gastrectomy (n = 63) and pylorus-preserving gastrectomy (n = 21). The primary outcome measure was postoperative quality of life assessed at 1 year using the Gastric Resection Syndrome Assessment Scale, Gastroparesis Cardinal Symptom Index (GSCI), and Pancreatic Exocrine Insufficiency Questionnaire (PEI-Q). Secondary outcomes included intraoperative and postoperative conditions, incidence of complications, and changes in nutritional status at 6 and 12 months post-surgery. Compared to the DG group, the PPG group exhibited fewer lymph node dissections [20 (17, 26) vs. 25 (19.5, 32), Z = 2.013, P = 0.052], shorter distances from the upper resection margin [2.0 (1.3, 3.0) vs. 3.5 (2.5, 4.75), Z = 4.664, P = 0.0002], and shorter distances from the lower resection margin [2.0 (1.4, 3.0) vs. 4.5 (4.0, 5.5), Z = 6.691, P < 0.001]. However, they experienced longer operative times [270 (240, 300) vs. 220 (187.5, 257.5), Z = 4.133, P = 0.0002], postoperative gas discharge times [4 (4, 5) vs. 4 (3, 4), Z = 5.96, P < 0.0001], and postoperative hospital stays [12 (10, 14) vs. 10 (9, 12), Z = 1.493, P = 0.0098]. One year postoperatively, patients in the PPG group demonstrated superior quality of life scores compared to the DG group in terms of the dumping symptom scale [1.0 (1.0, 1.33) vs. 2.5 (1.75, 2.5), Z = 7.192, P < 0.001], amount of food intake per meal [6 (6, 7) vs. 6 (4, 6), Z = 4.724, P = 0.0008], and meal quality scale [4.0 (3.67, 4.0) vs. 2.33 (1.67, 2.67), Z = 11.554, P < 0.0001]. Additionally, preoperative serum albumin levels were higher in the PPG group compared to the DG group [41.7 (40.3, 43) vs. 40.2 (39.15, 41.3), Z = 2.916, P = 0.006], and the PPG group had a lower rate of postoperative chemotherapy requirement (P = 0.024). Compared to distal gastrectomy (DG), pylorus-preserving gastrectomy (PPG) results in fewer dumping symptoms and an improved quality of life for patients following surgery. This makes PPG a highly favorable surgical option for treating stage T1 middle-third gastric cancer.